Testing a scaling relation between coherent radio emission and physical parameters of hot magnetic stars. Issue 4 (29th October 2022) - Das, Barnali; Chandra, Poonam; Shultz, Matt E; Leto, Paolo; Mikulášek, Zdeněk; Petit, Véronique; Wade, Gregg A
ABSTRACT: Coherent radio emission via electron cyclotron maser emission (ECME) from hot magnetic stars was discovered more than two decades ago, but the physical conditions that make the generation of ECME favourable remain uncertain. Only recently was an empirical relation, connecting ECME luminosity with the stellar magnetic field and temperature, proposed to explain what makes a hot magnetic star capable of producing ECME. This relation was, however, obtained with just 14 stars. Therefore, it is important to examine whether this relation is robust. With the aim of testing the robustness, we conducted radio observations of five hot magnetic stars. This led to the discovery of three more stars producing ECME. We find that the proposed scaling relation remains valid after the addition of the newly discovered stars. However, we discovered that the magnetic field and effective temperature correlate for T eff ≲ 16 kK (likely an artefact of the small sample size), rendering the proposed connection between ECME luminosity and T eff unreliable. By examining the empirical relation in light of the scaling law for incoherent radio emission, we arrive at the conclusion that both types of emission are powered by the same magnetospheric phenomenon. Like the incoherent emission, coherent radio emission is indifferent to T eff for late-B and A-type stars, but T eff appears to become important for early-B type stars, possibly due to higher absorption, or higher plasma density at the emission sites suppressing the production of the emission.